2015
DOI: 10.1371/journal.pone.0122747
|View full text |Cite
|
Sign up to set email alerts
|

Rural, Urban and Migrant Differences in Non-Communicable Disease Risk-Factors in Middle Income Countries: A Cross-Sectional Study of WHO-SAGE Data

Abstract: BackgroundUnderstanding how urbanisation and rural-urban migration influence risk-factors for non-communicable disease (NCD) is crucial for developing effective preventative strategies globally. This study compares NCD risk-factor prevalence in urban, rural and migrant populations in China, Ghana, India, Mexico, Russia and South Africa.MethodsStudy participants were 39,436 adults within the WHO Study on global AGEing and adult health (SAGE), surveyed 2007–2010. Risk ratios (RR) for each risk-factor were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 31 publications
7
104
0
1
Order By: Relevance
“…However, the trend was opposite a decade ago when the prevalence of smoking was reported more in urban areas (15.2% as compared to 13.7%) in a national survey (25). Similar trends have been seen in China, Ghana and India (26). The design of tobacco control policies in Pakistan may be a major contributing factor for causing this shift of smoking burden to rural areas.…”
Section: What Is Already Known On This Topicmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the trend was opposite a decade ago when the prevalence of smoking was reported more in urban areas (15.2% as compared to 13.7%) in a national survey (25). Similar trends have been seen in China, Ghana and India (26). The design of tobacco control policies in Pakistan may be a major contributing factor for causing this shift of smoking burden to rural areas.…”
Section: What Is Already Known On This Topicmentioning
confidence: 77%
“…In multivariate analysis for both sexes, being in one of the two older age groups (30-39, 40-49) increased odds of cigarette smoking compared with the youngest age group (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Twice as many rural women smoked cigarettes compared with urban women (1.6% compared with 0.8%), however in multivariate analyses, geography was not significantly associated with cigarette smoking in either sex [ Table 4].…”
Section: -Insert Table 3: Characteristics Of Included Men and Women-mentioning
confidence: 99%
“…16 Similar observations were reported in other Pacific, African and Caribbean countries. 13,[17][18] In contrast, Lin et al 19 reported high prevalence of diabetes in both rural and urban areas in Pacific Tongans. This suggests adoption of new lifestyle which is closely associated with urbanisation in certain countries might not be applicable to some indigenous populations who are at high risk of diabetes irrespective of the rural-urban status.…”
Section: Discussionmentioning
confidence: 96%
“…Kimbe town has witnessed an exponential rise of population by 500% in 30 years and is likely to quadruple the current figure by 2020 in view of increased industrial and mining activities which are linked to rural-urban migration. 9,12,13 The significance of this finding suggests rapid expansion of the population may have impact on in-50 creasing the risk of diabetes likely related to lifestyle changes related to modernisation. Findings of many studies have shown clearly a positive rural-urban gradient in prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid urbanization, rural-tourban migration, poor dietary habits, physical inactivity, sociocultural factors, and genetic predisposition all contribute to dyslipidemia [5]. The WHO Study on Global Aging and Adult Health carried out among 39,436 adults during 2007-2010 revealed that rural-urban migrants had a similar risk factor profile for non-communicable disease to the urban group, suggesting that exposure to urban environments may promote assimilation of health behavior regardless of previous life experiences [6]. This study was carried out to assess the prevalence of dyslipidemia among the elderly in slums of West Delhi.…”
Section: Introductionmentioning
confidence: 99%